Mean nocturnal baseline impedance: Influencing factors and diagnostic value in gastroesophageal reflux disease - Wang, Ning; Guo, Zi-Hao; Wu, Yan-Hong; Zhang, Chuan (Technology and health care, 2023)
BACKGROUND: At present, there are few studies related to mean nocturnal baseline impedance (MNBI), esophageal dynamic reflux monitoring, high-resolution esophageal manometry (HRM) parameter indexes, and its diagnostic value in gastroesophageal reflux disease (GERD). OBJECTIVE: To analyze the factors influencing MNBI and examine the diagnostic value of MNBI in GERD. METHODS: A retrospective analysis on 434 patients with typical reflux symptoms who underwent gastroscopy, 24-hour multichannel intraluminal impedance and pH monitoring (MII/pH) and HRM. They were divided into the conclusive evidence group (103 cases), borderline evidence group (229 cases), and exclusion evidence group (102 cases) according to the level of diagnostic evidence of GERD based on the Lyon Consensus. We analyzed the differences in MNBI, esophagitis grade, MII/pH and HRM index among the groups; the correlation between MNBI and the above indexes and its influence on MNBI; and to evaluate the diagnostic value of MNBI in GERD. RESULTS: There were significant differences in MNBI, Acid Exposure Time (AET) 4%, DeMeester score, and total reflux episodes among the three groups ( P < 0.001). EGJ contractile integral (EGJ-CI) of the conclusive evidence group and the borderline evidence group was significantly lower than that in the exclusion evidence group ( P < 0.001). MNBI was significantly and negatively correlated with age, BMI, AET 4%, DeMeester score, total reflux episodes, EGJ classification, esophageal motility abnormalities, and esophagitis grade (all P < 0.05), and significantly and positively correlated with EGJ-CI ( P < 0.001). Age, BMI, AET 4%, EGJ classification, EGJ-CI, and esophagitis grade had significant effects on MNBI ( P < 0.05); MNBI was used to diagnose GERD with a diagnostic cutoff of 2061 Ω , and AUC was 0.792 (sensitivity 74.9%, specificity 67.4%); MNBI was used to diagnose exclusion evidence group with a diagnostic cutoff of 2432 Ω , AUC was 0.774 (sensitivity 67.6%, specificity 72%). CONCLUSION: AET, EGJ-CI, and esophagitis grade are the most important influence factors of MNBI. MNBI has good diagnostic value in identifying conclusive GERD.